An ecosystem-based approach to assess the status of Mediterranean algae-dominated shallow rocky reefs. Issue 1 (15th April 2017) - Thibaut, Thierry; Blanfuné, Aurélie; Boudouresque, Charles F.; Personnic, Sébastien; Ruitton, Sandrine; Ballesteros, Enric; Bellan-Santini, Denise; Bianchi, Carlo Nike; Bussotti, Simona; Cebrian, Emma; Cheminée, Adrien; Culioli, Jean-Michel; et al.
Abstract: A conceptual model was constructed for the functioning the algae-dominated rocky reef ecosystem of the Mediterranean Sea. The Ecosystem-Based Quality Index (reef-EBQI) is based upon this model. This index meets the objectives of the EU Marine Strategy Framework Directive. It is based upon (i) the weighting of each compartment, according to its importance in the functioning of the ecosystem; (ii) biological parameters assessing the state of each compartment; (iii) the aggregation of these parameters, assessing the quality of the ecosystem functioning, for each site; (iv) and a Confidence Index measuring the reliability of the index, for each site. The reef-EBQI was used at 40 sites in the northwestern Mediterranean. It constitutes an efficient tool, because it is based upon a wide set of functional compartments, rather than upon just a few species; it is easy and inexpensive to implement, robust and not redundant with regard to already existing indices. Highlights: A conceptual model of functioning was developed for the rocky-reef ecosystem. The quality of the ecosystem was assessed on the basis of functional compartments. An Ecosystem-Based Quality Index (reef-EBQI) was developed. A confidence index measure the reliability of the reef-EBQI. The index was validated within 40 sites of the Mediterranean Sea.